NÃVEIS DE AÃ‡ÃšCARES E ATIVIDADE DE INVERTASES EM CANA-DE-AÃ‡ÃšCAR (Saccharum spp.) II. CULTIVARES SP70-1143 E SP-71-799 - Vieira, Irenice M. S.; Oliveira, Enio T. de; Gallo, Luiz A.; Batista, Telma F. C.; Rodrigues, Rosana C.; Crocomo, Otto J. (REVISTA DE AGRICULTURA, 2015)
NÃVEIS DE AÃ‡ÃšCARES E ATIVIDADE DE INVERTASES EM CANA-DE-AÃ‡ÃšCAR (Saccharum spp.) II. CULTIVARES SP70-1143 E SP-71-799